Substance Use, Pengetahuan akan AIDS, Hubungan Seks dalam Pengaruh Alkohol dan Obat-Obatan Terlarang, serta Perilaku Seks Berisiko pada Pria Heteroseksual - Wahyu Rahardjo (Jurnal Ilmiah Psikologi MIND SET, 2010)
Risky sexual behavior has become a global social phenomenon. One of its consequences is the increasing HIV/AIDS case. On the other hand, some variables, such as substance use, AIDS knowledge and sexual intercourse under the influence of substance use are attributed to risky sexual behavior. This study aims to examine the correlation between substance use, knowledge on AIDS, sexual intercourse under the influence of substance use and risky sexual behavior. 40 college heterosexual male students are collected as participants. Alcohol consumption as a substance use correlates with sexual intercourse under the influence of substance use, sexual intercourse with strangers, dating duration, and age of first time dating. Sexual intercourse under the influence of substance use correlates with dating duration. Some of risky sexual behaviors also correlate with other risky sexual behaviors. However, there is no correlation between knowledge of AIDS with other variables. Hence, other variables must be considered as predictors of risky sexual behavior to have more comprehensive mainframe.